The Catena in Marcum : a Byzantine anthology of early commentary on Mark - Lamb, William R. S. (Texts and Editions for New Testament Study, 2012)
The Catena in Marcum commonly attributed to Victor of Antioch, is the earliest anthology of patristic commentary on the gospel according to St Mark. Its compilation dates from the end of the fifth century and the beginning of the sixth century. Providing the first extended English translation, this book identifies the range of patristic sources employed by the editors, and the historiographical, literary and dogmatic concerns which informed the editing and compilation of this important text. It provides an invaluable resource for those interested in the history and development of the interpretation of Mark.